Find the best answers to your questions at Westonci.ca, where experts and enthusiasts provide accurate, reliable information. Connect with professionals ready to provide precise answers to your questions on our comprehensive Q&A platform. Get quick and reliable solutions to your questions from a community of experienced experts on our platform.
Sagot :
To determine the [tex]$x$[/tex]-intercepts of the quadratic function [tex]\( f(x) = (x+6)(x-3) \)[/tex], you need to find the values of [tex]\( x \)[/tex] where the function equals zero. This is achieved by setting [tex]\( f(x) = 0 \)[/tex] and solving for [tex]\( x \)[/tex].
1. Start with the given function:
[tex]\[ f(x) = (x+6)(x-3) \][/tex]
2. Set the function equal to zero to find the [tex]$x$[/tex]-intercepts:
[tex]\[ (x+6)(x-3) = 0 \][/tex]
3. Use the Zero Product Property, which states that if a product of factors is zero, at least one of the factors must be zero. Therefore, set each factor equal to zero and solve for [tex]\( x \)[/tex]:
[tex]\[ x + 6 = 0 \quad \text{or} \quad x - 3 = 0 \][/tex]
4. Solve each equation separately:
[tex]\[ x + 6 = 0 \quad \Rightarrow \quad x = -6 \][/tex]
[tex]\[ x - 3 = 0 \quad \Rightarrow \quad x = 3 \][/tex]
So, the [tex]$x$[/tex]-intercepts of the function are:
[tex]\[ (-6, 0) \quad \text{and} \quad (3, 0) \][/tex]
Among the given choices, the point [tex]\((-6, 0)\)[/tex] is listed. Therefore, the [tex]$x$[/tex]-intercept of the quadratic function [tex]\( f(x) = (x+6)(x-3) \)[/tex] that matches one of the given options is:
[tex]\[ (-6, 0) \][/tex]
Thus, the correct answer is:
[tex]\[ \boxed{(-6, 0)} \][/tex]
1. Start with the given function:
[tex]\[ f(x) = (x+6)(x-3) \][/tex]
2. Set the function equal to zero to find the [tex]$x$[/tex]-intercepts:
[tex]\[ (x+6)(x-3) = 0 \][/tex]
3. Use the Zero Product Property, which states that if a product of factors is zero, at least one of the factors must be zero. Therefore, set each factor equal to zero and solve for [tex]\( x \)[/tex]:
[tex]\[ x + 6 = 0 \quad \text{or} \quad x - 3 = 0 \][/tex]
4. Solve each equation separately:
[tex]\[ x + 6 = 0 \quad \Rightarrow \quad x = -6 \][/tex]
[tex]\[ x - 3 = 0 \quad \Rightarrow \quad x = 3 \][/tex]
So, the [tex]$x$[/tex]-intercepts of the function are:
[tex]\[ (-6, 0) \quad \text{and} \quad (3, 0) \][/tex]
Among the given choices, the point [tex]\((-6, 0)\)[/tex] is listed. Therefore, the [tex]$x$[/tex]-intercept of the quadratic function [tex]\( f(x) = (x+6)(x-3) \)[/tex] that matches one of the given options is:
[tex]\[ (-6, 0) \][/tex]
Thus, the correct answer is:
[tex]\[ \boxed{(-6, 0)} \][/tex]
Thanks for using our service. We're always here to provide accurate and up-to-date answers to all your queries. Thank you for choosing our platform. We're dedicated to providing the best answers for all your questions. Visit us again. Westonci.ca is your trusted source for answers. Visit us again to find more information on diverse topics.